2021
DOI: 10.1002/app.50557
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene/poly(ethylene terephthalate) microfibrillar reinforced composites manufactured by fused filament fabrication

Abstract: In the present work, microfibrillar composites (MFCs) consisting of polypropylene (PP) and poly(ethylene terephthalate) (PET) were successfully produced by melt extrusion and cold stretching. The resulting filaments were then printed using fused filament fabrication. The morphological results demonstrate that the highly oriented PET fibrils after stretching are still well preserved in the printed components. Since the printing process defines the alignment of the fibrils in the final component the fibers can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…During the melt extrusion, various shapes of RPET can be formed which can affect the mechanical properties of the blend 64 . It was revealed that increasing the weight ratio of RPET in the blend can enhance the shear stress in the compounding process leading to the formation of longer major axis elliptical shape 65,66 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the melt extrusion, various shapes of RPET can be formed which can affect the mechanical properties of the blend 64 . It was revealed that increasing the weight ratio of RPET in the blend can enhance the shear stress in the compounding process leading to the formation of longer major axis elliptical shape 65,66 …”
Section: Resultsmentioning
confidence: 99%
“…64 It was revealed that increasing the weight ratio of RPET in the blend can enhance the shear stress in the compounding process leading to the formation of longer major axis elliptical shape. 65,66 The SEM image of cryo-fractured surface of HOB shown in Figure 4B, exhibited microfibrils with almost uniform cross-section formed during blending. It is obvious that well oriented PET fibrils with a high aspect ratio was formed, suggesting that compatibilizer covers the PET particles during the mixing and prevents the coalescence in the drawing procedure.…”
Section: Morphological Structurementioning
confidence: 99%
“…PO/ PET blend is therefore with poor interfacial adhesion and two-phase morphology [15,16]. Although various compatibilizers [17,18] and new processing methods are used, microfibrillar reinforced composite [19,20], for instance, are developed; a valuable route for PE/PET or PP/PET blend recovery has not been satisfactorily established.…”
Section: Introductionmentioning
confidence: 99%
“…Fused filament fabrication (FFF) has attracted considerable attention as an effective tool due to its simplicity, low timeto-market, and freedom of design. [1][2][3][4] Although it is a decades technology, 5 FFF is one of the methods with the greatest potential to satisfy the design with various geometry of components and deposit multiple parts simultaneously. [6][7][8] In FFF, a thermoplastic filament is melted in a moving hot nozzle via heat conduction, and then the strand is deposited according to a laying pattern matched to the component.…”
Section: Introductionmentioning
confidence: 99%
“…Fused filament fabrication (FFF) has attracted considerable attention as an effective tool due to its simplicity, low time‐to‐market, and freedom of design 1–4 . Although it is a decades technology, 5 FFF is one of the methods with the greatest potential to satisfy the design with various geometry of components and deposit multiple parts simultaneously 6–8 .…”
Section: Introductionmentioning
confidence: 99%